SOCIAL STUDIES INSTRUCTIONAL IMPACTS ON UNDERGRADUATES’ DEMOCRATIC VALUES IN TERTIARY INSTITUTIONS IN KWARA STATE - Olokooba, Issa Nasiru; Lebari, Michael; yanne, Elizabeth Obiageli (African Journal of Social and Behavioural Sciences, 2025)
This study examined the impact of Social Studies instructions on undergraduates’ democratic values in tertiary institutions in Kwara State, Nigeria. The objectives of this study were to examine the manifestation of democratic values, the adequacy of Social Studies undergraduate benchmark in promoting democratic values, the extent to which Social Studies undergraduate participate in democratic processes and the impacts of Social Studies instruction on the development of democratic values in undergraduates in Kwara State. The population of the study was Social Studies undergraduates in Kwara State. The study adopted a descriptive survey design. 350 Social Studies undergraduates were sampled through the purposive sampling technique. The researcher’s designed questionnaire titled “Impact of Social Studies Instruction on Undergraduate Democratic Values Questionnaire was used as an instrument to elicit data from the respondents. Content validity was used to determine the validity of the instrument with a reliability coefficient of 0.87 using Pearson Product Moment Correlation. The findings of the study showed that the majority of Social Studies undergraduates in tertiary institutions actively participated in democratic processes. The findings suggested the need for continued emphasis on critical thinking skills in the Social Studies curriculum and the incorporation of community-based projects that promote democratic values and address local societal issues. The study also highlighted the impact of Social Studies instructions on undergraduate democratic values in Kwara State is positive. The study therefore, recommended, among others, that educational institutions should provide students with more opportunities for active participation in student unionism and associations, encouraging them to take leadership roles and engage in campus governance.